A taxonomic revision of the mealybug genus Ferrisia Fullaway (Hemiptera: Pseudococcidae), with descriptions of eight new species and a new genus - Kaydan, M. B.; Gullan, P. J. (Zootaxa, 2012)
The mealybug genus Ferrisia Fullaway is revised to include 18 species, based on morphological and molecular data. Wedistinguish the widespread pest species F. virgata (Cockerell) from morphologically similar species and provide a reviseddescription and illustration for the adult female of F. virgata. We resurrect Dactylopius dasylirii Cockerell stat. rev. fromsynonymy with Dactylopius virgatus Cockerell as Ferrisia dasylirii (Cockerell) and apply this name to many North Amer-ican and Caribbean populations previously recognised as F. virgata; F. dasylirii is the most difficult to distinguish mor-phologically from F. virgata and exhibits morphological and molecular variation among some populations. We designatea lectotype for D. dasylirii Cockerell. Eight new species of Ferrisia are described and illustrated based on the adult female,and named as Ferrisia colombiana sp. n., F. cristinae sp. n., F. ecuadorensis sp. n., F. kondoi sp. n., F. milleri sp. n., F.pitcairnia sp. n., F. uzinuri sp. n. and F. williamsi sp. n. The relationships of five of these new species and five namedspecies are discussed in relation to a previously published phylogenetic tree that was based on nucleotide sequence data.Taxonomically informative morphological features (such as the size, shape and position of discoidal pores associated withthe dorsal enlarged tubular ducts and the ventral oral-collar tubular ducts), identified for each of the genetic groups (clades)on the tree, are used to help to diagnose the species. We also describe and illustrate the adult female of a form of F. gilliGullan, found on Magnolia and some other host plants, that has numerous clusters of small ventral oral-collar ducts onthe body margins. For seven named species—F. claviseta (Lobdell), F. malvastra (McDaniel), F. meridionalis Williams,F. multiformis Granara de Willink, F. quaintancii (Tinsley), F. setosa (Lobdell) and F. terani Williams & Granara de Will-ink—we provide revised illustrations of the adult females as well as diagnostic morphological notes and information ondistribution and host plants. We also recognise Eurycoccus copallinae Ferris as a junior synonym (syn. n.) of Dactylopiusquaintancii Tinsley (now F. quaintancii) and designate a lectotype for E. copallinae. We include photographs of the liveappearance of the adult females of six Ferrisia species and also a key to all known species of Ferrisia based on the mor-phology of the adult females. We transfer the species currently known as Ferrisia floridana (Ferris) to a new monotypicgenus, Pseudoferrisia gen. n., as Pseudoferrisia floridana (Ferris) comb. n., and provide a description of the genus and its type species (Ferrisiana floridana Ferris), as well as a new illustration of the adult female.